2000
DOI: 10.1093/jexbot/51.343.249
|View full text |Cite
|
Sign up to set email alerts
|

Developmental pathway of somatic embryogenesis in Picea abies as revealed by time‐lapse tracking

Abstract: Several coniferous species can be propagated via somatic embryogenesis. This is a useful method for clonal propagation, but it can also be used for studying how embryo development is regulated in conifers. However, in conifers it is not known to what extent somatic and zygotic embryos develop similarly, because there has been little research on the origin and development of somatic embryos. A time-lapse tracking technique has been set up, and the development of more than 2000 single cells and few-celled aggreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
178
0
6

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 189 publications
(193 citation statements)
references
References 39 publications
9
178
0
6
Order By: Relevance
“…20 Using time-lapse tracking technique, we have characterised previously all the successive stages in this developmental pathway, including the stages of proembryogenic mass, proembryogenic mass-to-embryo transition, early embryogeny and late embryogeny. 21 We found that somatic embryo development of Norway spruce is similar to zygotic embryogeny of Pinaceae, even though embryo origin is different in each case (i.e., somatic cells in proembryogenic mass versus zygote). 21,22 Our more recent studies suggest that autophagic programmed cell death regulates active shape remodeling during both somatic and zygotic embryo development, 23,24 and that dysregulation of this cell death leads to embryonic aberrations.…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…20 Using time-lapse tracking technique, we have characterised previously all the successive stages in this developmental pathway, including the stages of proembryogenic mass, proembryogenic mass-to-embryo transition, early embryogeny and late embryogeny. 21 We found that somatic embryo development of Norway spruce is similar to zygotic embryogeny of Pinaceae, even though embryo origin is different in each case (i.e., somatic cells in proembryogenic mass versus zygote). 21,22 Our more recent studies suggest that autophagic programmed cell death regulates active shape remodeling during both somatic and zygotic embryo development, 23,24 and that dysregulation of this cell death leads to embryonic aberrations.…”
Section: Introductionmentioning
confidence: 70%
“…21 We found that somatic embryo development of Norway spruce is similar to zygotic embryogeny of Pinaceae, even though embryo origin is different in each case (i.e., somatic cells in proembryogenic mass versus zygote). 21,22 Our more recent studies suggest that autophagic programmed cell death regulates active shape remodeling during both somatic and zygotic embryo development, 23,24 and that dysregulation of this cell death leads to embryonic aberrations. 25 Using somatic embryos of Norway spruce, we characterized the cell biological pathway of autophagic death in the suspensor, a temporal structure, which is composed of the cells at successive steps of the death pathway and is finally eliminated during late embryogeny.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…They can be distinguished from the surrounding cells/callus by their relatively high nucleus to cytoplasm ratio, a nucleus with a single large nucleolus and relatively low heterochromatin levels, the presence of fragmented vacuoles, and by their callose‐containing cell walls (Verdeil et al., 2007). Although we have a good idea about the types of cells that form somatic embryos in vitro (Filonova, Bozhkov, & Arnold, 2000; Toonen et al., 1994) and the cellular characteristics of these cells (Emons, 1994; Verdeil et al., 2007; Yeung, 1995), the process remains largely undescribed at the molecular level. High throughput expression analyses have been used to identify characteristics of embryogenic explants (Salvo, Hirsch, Buell, Kaeppler, & Kaeppler, 2014; Trontin, Klimaszewska, Morel, Hargreaves, & Lelu‐Walter, 2016; Wickramasuriya & Dunwell, 2015; Yang et al., 2012), but most studies use whole explants, which contain a complex mixture of tissues and cell types, making it difficult to specifically assign molecular identities to embryogenic cells.…”
Section: Definitions and Conceptsmentioning
confidence: 99%
“…For initiation of embryogenic callus on explants of all spruce and larch species are generally used the basal medium supplemented with an auxin (9 µM 2.4-D) and a cytokinin (4.4 µM BAP) (Hakman et al 1985;Becwar et al 1987;Bozhkov and von Arnold 1998;Filonova et al 2000a). In this experiment, those hormones also usually proved to be sufficient for embryogenic callus initiation in those species.…”
Section: Embryogenic Callus Initiationmentioning
confidence: 99%